Inovação e empreendedorismo em empresas no metaverso - Mateus, Gustavo de Almeida (2024)
This research sought to understand the phenomenon of entrepreneurship by applying the metaverse and highlighting the innovation process and the opportunities that companies in this emerging digital environment use. The main objective was to investigate how technology and entertainment companies in Brazil, focusing on the case of Uplandme, Inc., Inc., use the metaverse to drive entrepreneurship and innovation, identifying challenges and opportunities. Regarding the methodological aspects, the exploratory research and qualitative approach were based on the case study method, combining semi-structured interviews with documentary analysis to understand the strategies and business practices of Uplandme, Inc., Inc. Triangulation of the data ensured a comprehensive and reliable analysis. The findings showed that the metaverse enables the creation of new business models based on disruptive technologies such as blockchain and NFTs and promotes immersive experiences for users. Among the main challenges, technical issues such as platform interoperability and regulatory barriers associated with using cryptoassets were highlighted. Despite this, the metaverse has catalyzed innovation and entrepreneurship, creating ways to interact with consumers and markets. It was concluded that, although still in its early stages, the metaverse has great potential to transform businesses and drive economic growth. The survey reinforces the importance of collaboration between academia, industry, and government to overcome challenges and maximize the benefits of this digital environment. Managers interested in exploring the metaverse should adopt experimental and collaborative approaches to prepare their companies for this ever-evolving scenario